Challenges and Perspectives of Formative Research in Times of Artificial Intelligence (Docentes 2.0 Journal, 2026)
Over the past two decades, formative research has become a key process in higher education, integrating teaching, knowledge generation, and the development of students' research skills. In this context, the objective of this study was to examine the current landscape, main challenges, and future prospects of formative research regarding the use of artificial intelligence (AI). The research was conducted within the humanistic paradigm, employing a systematic method and a qualitative approach, with a narrative topical design and an informative documentary style. Twenty scientific articles published between 2020 and 2025 and indexed in Scopus, Web of Science, and SciELO were analyzed. The analysis allowed for the systematization of the theoretical, methodological, and ethical approaches related to the integration of AI in educational and research processes. The results demonstrate that these technologies strengthen research skills, promote personalized learning, and enable the use of educational analytics for monitoring academic performance. However, challenges associated with technological dependence, risks to academic integrity, and the persistence of the digital divide were also identified. Epistemological tensions related to authorship, validity, and reliability of algorithmically generated content were also observed. In short, formative research in the age of AI is an emerging field that requires responsible pedagogical integration, critical digital literacy, and institutional policies that promote the ethical use of these technologies.
Keywords: formative research; artificial intelligence; digital literacy; academic ethics; systematic review